Doubt in change of basis matrix [closed]

Let $A=\{(1,0,5) (4, 5,5)(1,1,4)\}; B= \{(1,3,2)(-2,-1,1)(1,2,3) \}$. To find change of basis matrix.

$\boxed{ M_{A\to B} = M_{A\to e}M_{e\to B} } ---(1)\\= \begin{pmatrix} 1 & 4 & 1 \\ 0 & 5 & 1 \\ 5 & 5 & 4 \end{pmatrix}^{-1} \begin {pmatrix} 1 & -2 & 1 \\ 3 & -1 & 2 \\ 2 & 1 & 3 \end {pmatrix} = \boxed {\begin {pmatrix} -2 & -2 & -1 \\ 0 & -1 & 0 \\ 3 & 4 & 2 \end {pmatrix} } -----(2)$

Is equation (1) correct??? or it is $M_{A \to B} = M_{e \to B} M_{A \to e}$ as given in solution part of LINK:- How to construct change of basis matrix (I am confused here pls correct me if i am wrong...)

To reconfirm i did it in following way:-

to find coordinates of B interms of A

$(1,3,2)= a(1,0,5)+b(4,5,5)+c(1,1,4)=(a+4b+c,5b+c,5a+5b+4c)=[-2,0,3]_B$

Similarly $(-2,-1,4) \sim [-2,-1,4]_B \\ (1,2,3) \sim [-1,0,2]_B$

THis boils down to same above matrix by (2) closed as off-topic by user99914, Saad, Gibbs, Taroccoesbrocco, BrahadeeshJun 23 '18 at 10:37

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Community, Saad, Gibbs, Taroccoesbrocco, Brahadeesh
If this question can be reworded to fit the rules in the help center, please edit the question.

• There is also a typo, in your hypotesis it should be $M_{A\to B} = M_{e\to A}M_{B\to e}$ but how explained $M_{e\to A}M_{B\to e}=M_{B\to A}$. – user Jun 20 '18 at 10:45
• Could you define what you mean by "change of basis matrix"? Because there is closely related "change of coordinate matrix", which is precisely the inverse of that. Maybe the confusion is there. – A.Γ. Jun 20 '18 at 11:03
• @A.Γ. Sir i did not go deep. I am at linear transformations part of linear algebra. Change of basis matrix or change of coordinate matrix not same? pls elaborate... Change of basis matrix -- $[v]_B = Q^{-1}_{A \to B} [v]_A$ – Magneto Jun 20 '18 at 11:08
• Your first way looks ok to me, the second is unclear, how did you get those matrices in "matrix method"? – A.Γ. Jun 20 '18 at 11:52
• Got it. I misundersttod change of basis matrix. Re-read textbook again. Pls see my last below comment. – Magneto Jun 20 '18 at 12:38

We need

$$M_{A\to B} = M_{e\to B}M_{A\to e}$$

that is

$$\begin {pmatrix} 1 & -2 & 1 \\ 3 & -1 & 2 \\ 2 & 1 & 3 \end {pmatrix}^{-1}\begin{pmatrix} 1 & 4 & 1 \\ 0 & 5 & 1 \\ 5 & 5 & 4 \end{pmatrix}$$

indeed the first matrix takes a vector in basis $A$ to the standard basis and the second takes a vector in the standard basis to the basis $B$, therefore the product matrix takes a vector from basis $A$ to basis $B$.

• can u pls have a look at part 2 or the other way i did to find change of basis matrix. To find change of basis matrix i followed - output basis = express in terms of input basis – Magneto Jun 20 '18 at 10:29
• @anirudhb The matrix M you have found with tour method changes basis from B to A, indeed we have $M(1,0,0)=(-2,0,3)$ which are the components of $(1,3,2)$ in the basis $A$. – user Jun 20 '18 at 10:36
• I understood matrix method. Actually i am bit confused about other way. For ex., @gimusi take $M_{e \to A}. \\$$(1,0,5) = 1e_1+0e_2+5e_3 \\$... like that i will express output basis vector interms of input basis vector. But i find using same way, output basis B vector = interms of input basis A vectors linear comination, i am gettting $M^{-1}$. Pls clarify. – Magneto Jun 20 '18 at 10:47
• $M_{e \to A} \cdot (1,0,5)$ simply gives the components for $(1,0,5)$ in the basis $A$, I don't understand your doubts on that. Please explain better. – user Jun 20 '18 at 10:51
• Sir i uploaded my worked out image. Pls have a look – Magneto Jun 20 '18 at 11:04